Antibiotic Sensitivity Testing of Bacteria Isolated from Patients Suspected of Urinary Tract Infection: Uji Sensitivitas Antibiotik terhadap Bakteri yang Diisolasi dari Pasien Diduga Infeksi Saluran Kemih - Erpi Nurdin; Suanbani, Dawika; Mukhtasyam Zuchrullah (Jurusan Biologi Universitas Negeri Makassar, 2024)
Urinary tract infections (UTIs) is a condition wherein inflammation occurs, caused by the proliferation of microorganisms in the human urinary tract. Antibiotics are the main choice in treating UTIs, the aim of giving antibiotics is to treat acute infections and prevent urosepsis. However, deviant use of antibiotics will reduce the sensitivity of antibiotics to bacteria. The aim of this study was to determine the sensitivity of bacteria to antibiotics from urine specimens of patients with suspected urinary tract infections (UTIs). The examination begins with the determination of the bacterial species and continues with the sensitivity test of the Kirby-Bauer diffusion method, looking at the barrier zone of each antibiotic. The observation results showed that there were 6 types of bacteria found from the urine culture results of patients with suspected urinary tract infections, with the most types of bacteria being gram positive S. aureus in 13 cases (40%), gram negative E. coli in 6 cases (18%), K. oxytoca and E. aerogenes were 5 cases (15%). According to the results of the antibiotic sensitivity test, each one shows the percentage of sensitive antibiotics. Ciprofloxacin is 100% against E. coli, K. oxytoca, P. mirabilis, 60% against E. aerogenes and 46% against S. aureus. Gentamicin is 100% against E. coli, K. oxytoca, P. mirabilis. Ampicillin is 83% against E. coli, 60% against S. epidermidis. Amoxicillin is 66% against E. coli. In conclusion, based on test results, Ciprofloxacin has better sensitivity, followed by gentamicin, ampicillin and amoxicillin. Keywords: antibiotics, sensitivity testing, urinary tract infection